Sistem Informasi Geografis Pemetaan Daerah Aliran Sungai Berbasis Web - Rahayu, Sitta; Piarsa, I Nyoman; Buana, Putu Wira (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 2 Agustus 2016DO - 10.24843/LKJITI.2016.v07.i02.p01, 2016)
Watershed management becomes very important because the more maintained its watershed, the risk for disasters caused by the overflowing river became smaller. Watershed management could be done if the information on that watershed could be complete, but untill this day, the available information was lacking. This condition caused the difficulty of data collected, so required a system that could be used to perform watershed data processing. A system that to be used is Geographic Information Systems Watershed Mapping. This system  is a Web-based system that can be used for collected data and mapping the watershed using a map from Google Maps. Features polyline which was owned by Google Maps can be used to describe a network of rivers and long inundation, library geometry was used to calculate the length of polylines, feature marker was used to describe the location of the dam and the point was prone to flooding of a river and features a polygon used to describe the watershed. This system can collected data watershed in two ways, namely digitization and input the coordinates that can be done by the admin. Results from watershed data can provide information to the user about the location of the dam along with its description, the river network in the watershed, a point prone to flooding, inundation and limit the length of the watershed and its description.
Keywords: DAS, Sistem Informasi Geografis, Google Maps, Web